DESIGN AND IMPLEMENTATION OF ELECTRONIC LOGGING INSTRUMENT TO HELP SCIENTIFIC DIVER IN CORAL REEF MONITORING - Kusuma, Hollanda Arief; Jaya, Indra; Manik, Henry Munandar (Marine Research in Indonesia, 2016)
Indonesia is situated in the Coral Triangle region that has the world?s highest coral reef biodiversity. Therefore, coral reef monitoring needs to be conducted regularly to assess the condition of coral reef ecosystem for management purpose. There are several coral reef monitoring methods available such as the line intercept transect (LIT), point intercept transect (PIT), photo transect, belt transect and benthic towed-diver. In Indonesia, LIT and PIT are the most commonly used methods for coral monitoring. However, there is a main disadvantage when collecting data using these methods, that is scientific divers need to spend hours to input the data after dives. Here, we introduce an electronic logging instrument called Coral Input Data Instrument that helps to decrease the input data time by employing a look-up table system that simplifies data input process by replacing text with numerical coding. In addition, water quality data such as temperature, depth and visibility also are embedded in the electronic logging instrument. The instrument hardware consists of Arduino Mega 2560, keypad 4x3, LCD Module 16x2 character, real time clock, temperature sensor, pressure sensor, visibility sensor and micro SD card module. Arduino IDE 1.6.5 software is used to program the microcontroller. In this paper, we describe the design and implementation of the instrument in the field.